Tumbler and Workplace Position: Representation and Distinction in Digital Meme Culture - Yuniarta, Ajeng; Khairunnisa, Khansa Vitria; Wulandari, Dini Rahma; Priohandoko, Rafli Aditya (Universitas Brawijaya, 2025)
In today’s digital culture, everyday objects such as tumblers have become symbols of social identity, mediated through memes. This study analyzes memes in social media, especially Instagram posts that show “Kasta Tumbler di Tempat Kerja” shared by an account @luarsekolah, which represents hierarchical position in the workplace through tumbler brand choices. Using Pierre Bourdieu’s theory of distinction and Stuart Hall’s concept of representation, this study examines how brand preferences in choosing tumbler reflect job positions and memes' role as a medium of social criticism in the context of digital culture. Through content analysis and contextual interpretation, the findings of the study highlight how tumbler is not only seen as a bottle only, but also shows lifestyle, social status, and identity in the digital era. In the end, someone’s tumbler choice not only reflects individual preferences, but also social status and how they want to be seen in the community.